Scour and Erosion 2016
DOI: 10.1201/9781315375045-34
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical erosion modelling of Baydaratskaya Bay, Russia with COSMOS

Abstract: Rapid coastal erosion threatens Arctic coastal infrastructure, including communities and industrial installations. Erosion of permafrost depends on numerous processes, including thermal and mechanical behaviour of frozen and unfrozen soil, nearshore hydrodynamics, atmospheric forcing, and the presence of sea ice. The quantification and numerical modelling of these processes is essential to predicting Arctic coastal erosion. This paper presents a case study of Baydaratskaya Bay, Russia, using the COSMOS numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…When a frozen bluff starts to melt, the mechanical strength of the soil is reduced. At some point, the stability of the slope cannot be maintained, and slope slipping occurs [16]. It was observed that thermodenudation could contribute up to 0.4 m of coastal retreat per year in the Kara Sea, where bluffs are mostly silt and silty clay [17].…”
Section: Introductionmentioning
confidence: 99%
“…When a frozen bluff starts to melt, the mechanical strength of the soil is reduced. At some point, the stability of the slope cannot be maintained, and slope slipping occurs [16]. It was observed that thermodenudation could contribute up to 0.4 m of coastal retreat per year in the Kara Sea, where bluffs are mostly silt and silty clay [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, local bathymetry can be used for validating the mapping of landfast sea ice stability with inter-ferometric synthetic aperture radar (Dammann et al, 2019). Further, coastal bathymetry and water level are important parameters for determining rates of coastal erosion (e.g., Barnhart et al, 2014;Pearson et al, 2016), and an improvement of local bathymetry will therefore help to improve model forecasts of coastal erosion in the Laptev Sea region (e.g., Rolph et al, 2021). In addition, for determining the extent of subsea permafrost, knowledge of water depth and sea surface morphology is essential.…”
Section: Potential Applications and Usage Of The Data Setsmentioning
confidence: 99%
“…Further, coastal bathymetry and water level are important parameters for determining rates of coastal erosion (e.g. Barnhart et al, 2014;Pearson et al, 2016) and an improvement of local bathymetry will therefore help to improve model forecasts of coastal erosion in the Laptev Sea region (e.g. Rolph et al, 2021).…”
Section: Potential Applications and Usage Of The Data Setsmentioning
confidence: 99%